An evolutionary algorithm for unicast/multicast traffic engineering - Rocha, Miguel (2008)
A number of Traffic Engineering (TE) approaches have been recently proposed to improve the performance of network routing protocols, both developed over MPLS and intra-domain protocols such as OSPF. In this work, a TE approach is proposed for routing optimization in scenarios where unicast and multicast demands are simultaneously present. Evolutionary Algorithms are used as the optimization engine with overall network congestion as the objective function. The optimization aim is to reach a set of (near-)optimal weights to configure the OSPF protocol, both in its standard version and also considering the possibility of using multitopology variants. The results show that the proposed optimization approach is able to obtain networks with low congestion, even under scenarios with heavy unicast/multicast demands.